The analysis of the state of development of devices for cleaning orbits in near-Earth space from large-sized space debris objects - V. I. Trushlyakov; V. V. Yudintsev; V. A. Urbansky; S. Yu. Onishchuk (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The state of near-Earth space pollution is considered, including the dynamics of growth of this pollution. Presented current information on the launch of nano-satellites, which is an additional factor in the pollution of low earth orbit. On the basis of open information, the analysis of the development of Russian and foreign approaches to the most polluted orbits cleaning, including technological experiments with the use of various means of capture is carried out. For different capture devices the options of towing space debris objects to the disposal orbit are considered.